The Influence of Educational Level, Type of Job, and Community Income on Community Participation in Waste Management in West Payakumbuh District - Nifriza, Ifna; Dari, Diana Wulan; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto; Daharnis, Daharnis (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Effective urban waste management is crucial, encompassing various dimensions such as financial, technical, legal, environmental, spatial planning, socio-cultural aspects, and stakeholder involvement. The household waste management landfill in Regional Payakumbuh is currently overcapacity, and the city lacks an independent waste landfill. This quantitative research utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3.0 to analyze data, a method within Structural Equation Modeling (SEM). The study population consists of 120 households in the Talang Payakumbuh Barat neighborhood, selected using proportional random sampling. Results indicate that the education level of the West Payakumbuh community positively influences waste management. This is supported by a P value of 0.044 (< 0.05), with a t-statistic of 1.786 (lower than 1.96). The original sample value of 0.188 is positive, leading to the acceptance of hypothesis H1. Similarly, the type of occupation significantly and positively influences community participation in waste management in Payakumbuh, supported by a P value of 0.022 (< 0.05) and a t-statistic of 4.351 (> 1.96). The original sample value of 0.463 is positive, confirming the acceptance of hypothesis H2. Additionally, community income has a positive and significant impact on their participation in waste management in Payakumbuh, as evidenced by a P value of 0.031 (< 0.05), a t-statistic of 2.292 (> 1.96), and an original sample value of 0.031. Hence, hypothesis H3 is accepted. Community participation in waste management in Payakumbuh is also influenced by social and cultural factors. The diversity in educational backgrounds and occupations presents unique challenges, contributing to the creation of a clean and comfortable city environment. This research emphasizes the need for integrated waste management strategies and community involvement to address the waste disposal challenges faced by Payakumbuh.